2016
DOI: 10.1007/s10546-016-0147-8
|View full text |Cite
|
Sign up to set email alerts
|

Drag and Bulk Transfer Coefficients Over Water Surfaces in Light Winds

Abstract: The drag coefficient (C D), experimentally determined from observed wind speed and surface stress, has been reported to increase in the low wind-speed range (< 3 m s −1) as wind speed becomes smaller. However, until now, the exact causes for its occurrence have not been determined. Here, possible causes for increased C D values in near-calm conditions are examined using high quality datasets selected from three-year continuous measurements obtained from the centre of Lake Kasumigaura, the second largest lake i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
31
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 76 publications
(84 reference statements)
9
31
3
Order By: Relevance
“…a). Under high wind regimes, the calibrated value (~2 × 10 −3 ) and the almost linear variation of the transfer coefficients are in agreement with reported measurements (Graf and Prost ; Merzi and Graf ; Mahrt et al ; Babanin and Makin ; Toffoli et al ; Wei et al ). Although the transfer coefficient values are consistent with other studies, there is a shift in the wind speed under which these minima are observed.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…a). Under high wind regimes, the calibrated value (~2 × 10 −3 ) and the almost linear variation of the transfer coefficients are in agreement with reported measurements (Graf and Prost ; Merzi and Graf ; Mahrt et al ; Babanin and Makin ; Toffoli et al ; Wei et al ). Although the transfer coefficient values are consistent with other studies, there is a shift in the wind speed under which these minima are observed.…”
Section: Discussionsupporting
confidence: 90%
“…To verify the calibration factors, we compare the shape and range of these curves with some measurements taken over water. The general form of theses curves is similar to the measured values over inland and open waters (e.g., Wüest and Lorke ; Wei et al ). As we obtained lower values for both C m 2 and C q 1 than Zeng et al (), the calibrated transport coefficients are smaller (higher) at low (high) winds than the uncalibrated coefficients in Fig.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…However, the kinetic factor is not very sensitive to wind speed, varying only slightly, from 6.9‰ at 10 m s −1 to 6.0‰ at 3 m s −1 , according to the theory of Merlivat and Jouzel (). The Dalton number of evaporation, a measure of the intensity of turbulent exchange of water vapor between the water surface and the overlaying air layer, does not seem to depend on lake size either (Wei et al, ; Xiao et al, ). Therefore, factors other than levels of turbulence, such as the compensating effect noted below, may be a more plausible explanation for why the LK ε k works in some situations but not in others.…”
Section: Discussionmentioning
confidence: 99%